(3GdeYdheGJ h OhQgG aj OYe h GJNGO GdbQGQ GdGSJQGJjLj (B/s - (3eHQhc GHQGgje, GdSYjOs ((3eUQ (B:s (3GdeLehYI GdYQHjI ddJOQjH h GdfTQ ,s, 2013)
(3JYQja GdeYdheGJ h NUGFUgG h echfGJgG h GfhGY eUGOQ GdeYdheGJ h GdGOGQI GdGSJQGJjLjI h GdJNWjW GdGSJQGJjLj h OhQ GdeYdheGJ aj fXe OYe h GJNGP GdbQGQ GdGSJQGJjLj s
Keywords: (3GdGOGQIs; (3GdJNWjW GdGSJQGJjLj s; (3GdeYdheGJs